SAT0544 Comparing the clinical profile of adults and children with behÇet's syndrome in the uk. (12th June 2018) - Myers, S.; Makmur, E.; Hanns, L.; Huskard, D.; Brogan, P.; Ambrose, N.
Abstract : Background: Behçet's syndrome (BS) is a rare multi-system inflammatory disorder and most commonly presents in young adults. Clinical phenotypic variance across geographical regions is recognised but there has been no UK publication assessing UK BS patients' variance by age groups. BS is primarily a clinical diagnosis, and there is significant diagnostic delay in the UK. Exploration of the phenotype in UK adults and children may help clinicians diagnose BS more effectively. Objectives: Describe and compare the clinical features of adults and children with BS in a UK population. Methods: We examined and compared two cumulative databases of clinical features of BS patients. The paediatric database was collected Great Ormond Street Hospital for Children, London (n=46). The adult database was collected at the Hammersmith Hospital, London (n=560). Results: Oral ulcers were common for both paediatric (97.8%) and adult (96.6%) populations. Genital ulceration also did not differ between paediatric (73.9%) and adult (75.7%) groups. Eye involvement was rare in children (4.3%) versus adults (37%) (p<0.001). Skin involvement was more common in the adult cohort (55.4% vs. 21.7%, p<0.001). There was a trend towards increased vascular involvement in adults (17.5%) versus children (6.5%). The children had higher gastrointestinal involvement compared to adults (21.7% vs. 4.5%, p<0.001) Conclusions: Paediatric BS patients displayed less ocular and skin manifestations compared to the adult BS patients. The BS UK phenotype differs from international cohorts. This information will be valuable in helping clinicians diagnose BS in UK adult and paediatric populations. Disclosure of Interest: None declared